Perancangan E-Katalog Brand Emonstore - Rafika Duri; Dwi Mutia Sari (Lembaga Pengembangan Kinerja Dosen, 2023)
Emonstore which was established in 2020 was carried out from social media and also opened a boot in front of the post office, Jalan Garuda no.20 Lubuklinggau City, selling the Emonstore brand through promotional supporting information media with E-catalogs. This research makes promotional media that contains information data about products and attracts consumers through the right promotional media so that in the future it is easily recognized by consumers and increases sales results. The design of the Emonstore E-catalog is made based on sources, namely in the form of data that has been collected through interviews with owners. The purpose of designing is to design the right promotional media according to the target audience of Emonstore. Promotional media in the form of a catalog makes it easier for consumers to see products, because the catalog designed contains product information data. The purpose of promotion is to inform an audience who do not yet know the product or service being promoted. The writing is designed using the glass box approach. Emonstore catalog, it is evident that the E-catalog's design was created using the idea of Emonstore's attributes.